Obtenção e caracterização físico-química de complexos supramoleculares de óleo essencial e substância isolada em ciclodextrinas - Menezes, Paula dos Passos (2015)
The essential oils, which are secondary metabolites produced by plants. These metabolites are part of the group of terpenes. Such organic molecules are characterized by presenting important pharmacological activities such as anti-inflammatory, antinociceptive, antimicrobial, among others. Thus, the essential oil of Hyptis pectinata (EOHP), a native fragrant plant of the states of Alagoas and Sergipe and widely used by the population, has attracted attention of researchers in order to validate its popular use. In addition, the isopulegol (ISOP), a major monoterpene in the industry for their flavoring properties and medicinal has been the subject of research in scientific research. However, EOHP present ISOP and the physico-chemical characteristics and limited water solubility, high volatilization photosensitivity and easy oxidation. In this perspective, an alternative to preserve the characteristics of these substances is the formation of supramolecular complexes involving cyclodextrins (CDs). The CDs have a molecular structure suitable for the formation of inclusion complexes since they have polar and hydrophilic surface cavity. Thus, the inclusion complex of essential oils and CDs improve the physico-chemical properties of these molecules to optimize the pharmacological activity thereof. Hence, the aim of this study was to identify the chemical constituents of OEHP by gas chromatography coupled to mass spectrometry with flame detector (GC-MS/FID) and from there to prepare the samples with β -CD and ISOP in the α- and β-CD by the methods of the physical mixture (PM), paste complexation (PC) and slurry complexation (SC). Furthermore, the physico-chemical characterization of the samples through the techniques of differential scanning calorimetry (DSC) was performed thermogravimetry/derivative thermogravimetry (TGA/DTG) absorption spectrophotometry in the infrared Fourier transform spectroscopy (FT-IR) scanning electron microscopy, X-ray diffraction (XRD), complexation efficiency by GC-MS/FID, pharmacological test formalin with the best complex obtained from OEHP and study of molecular modeling (docking) to isopulegol and CDs. Based on these results, we observed three major constituents in OEHP, (E) -caryophyllene (54.07%), caryophyllene oxide (14.91%) and germacrene-D (7.46%). The results of physicochemical characterization showed that the EC was the best method to complex (E)-caryophyllene and germacrene-D, caryophyllene oxide has not been complexed and this may be related to its low affinity for the cavity of β- CD. The formalin test showed a better antinociceptive and anti-inflammatory OEHP / β-CD when compared with pure EOHP that can be attributed to the high percentage of (E) -caryophyllene complexed. Regarding isopulegol, it was observed that α-CD complexes more stable inclusion of the β-CD, as showed in the docking analysis and PC/α-CD gave a higher ratio of complexing with respect to PM and SC. But the SC obtained with β-CD showed the highest molecular inclusion. Thus, the techniques used were efficient in the complexation of EOHP and ISOP.